DAMPAK KEKERASAN SEKSUAL PADA REMAJA TERHADAP PERKEMBANGAN CITA-CITA - Suryani, Aprilina; Ardi Ardani, Tristiardi (Lafadz Jaya Publisher, 2024)
This article provides an in-depth discussion on the impact of sexual violence on the development of life goals in adolescents, using a qualitative approach supported by secondary data from literature sources. Adolescence is a crucial period for identity formation and setting life goals. However, traumatic experiences such as sexual violence often disrupt this developmental process. The analysis shows that adolescent victims face serious psychological challenges, including depression, anxiety, and a loss of self-confidence—factors that significantly diminish their motivation and ability to pursue their dreams. Moreover, social stigma and inadequate support systems further exacerbate their condition. The study emphasizes the vital role of family, social environments, and professional counselors in offering emotional support and psychological guidance. Consistent and empathetic support can be a pivotal element in their mental recovery and in reigniting their aspirations. The article advocates for greater public awareness, trauma-informed interventions, and holistic support strategies to assist adolescent survivors of sexual violence in rebuilding their sense of self and purpose.